Edukasi Pemakaian Plastik Sebagai Kemasan Makanan Dan Minuman Serta Risikonya Terhadap Kesehatan Pada Komunitas di Kecamatan Bungus Teluk Kabung, Padang - Cimi Ilmiawati; Mohamad Reza; Rahmatini Rahmatini; Erlina Rustam (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2016)
Environmental exposure to plasticizers, such as phthalate and bisphenol-A, has wide impact on human health particularly in developmental stages, rendering fetus and children as the most susceptible populations. The route of exposure is mostly by ingesting contaminated foods and drinks. Plastics are widely used by the general public as food wrapping and beverage container. There are various kinds of plastics in terms of thermal stability and compositions. Knowing how to choose and to use the right kind of plastics that is relatively safe for contact with foods and drinks is important for each members of community to safeguard against the health-risks imposed by certain chemicals in plastics.